PERAN MODAL SOSIAL DALAM PENANAMAN NILAI TOLERANSI DI DESA MELILING KECAMATAN KERAMBITAN KABUPATEN TABANAN - Aroyani, Aspi Nur; Suka Arjawa, I Gst PT Bagus; Mahadewi, Ni Made Anggita Sastri (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
His study analyzes and describes the role of social capital owned by the Meliling Village community in instilling a value of tolerance. The theory used is Robert Putnam's theory of social capital..The results of this study indicate that the tolerance that grows in the Meliling Village community is manifested through trust, norms, and networks. Trust is in the form of giving food (fruit and cakes) to people of different religions and making non-Muslims as teaching staff at the Bali Bina Insani Islamic boarding school. The norm is in the form of mutual understanding, providing space for other religions to carry out worship, and helping each other to ease the economy of the Meliling community. The network consists of mobile village heads and Hindu communities who often attend recitation events and hospitality activities. Keywords: tolerance, social capital, trust, norms, and networks.